(+)-Magnolin Enhances Melanogenesis in Melanoma Cells and Three-Dimensional Human Skin Equivalent; Involvement of PKA and p38 MAPK Signaling Pathways - Uto, Takuhiro; Tung, Nguyen Huu; Ohta, Tomoe; Shoyama, Yukihiro (Planta Medica, 2022)
Magnoliae Flos is a traditional herbal medicine used to treat nasal congestion associated with headache, empyema, and allergic rhinitis. In our preliminary screening of crude drugs used in Japanese Kampo formulas for melanin synthesis, the methanol extract of Magnoliae Flos was found to exhibit strong melanin synthesis activity. However, there have been no studies evaluating the effects of Magnoliae Flos or its constituents on melanogenesis. The present study aimed to isolate the active compounds from Magnoliae Flos that activate melanin synthesis in melanoma cells and three-dimensional human skin equivalent, and to investigate the molecular mechanism underlying melanin induction. The methanol extract of Magnoliae Flos induced an increase of melanin content in both B16-F1 and HMV-II cells. A comparison of melanin induction by three fractions prepared from the extract showed that the ethyl acetate fraction markedly induced melanin synthesis. Bioassay-guided separation of the ethyl acetate fraction resulted in the isolation of seven lignans (1 – 7). Among them, (+)-magnolin (5) strongly induced melanin synthesis and intracellular tyrosinase activity. Furthermore, the ethyl acetate fraction and 5 clearly induced melanin content in a three-dimensional human skin equivalent. Molecular analysis revealed that 5 triggered the protein expression of tyrosinase, tyrosinase-related protein-1, and tyrosinase-related protein-2. Further analysis of transcriptional factors and signaling pathways demonstrated that 5 induces the protein expression of tyrosinase, tyrosinase-related protein-1, and tyrosinase-related protein-2 activated by the protein kinase A- and p38 mitogen-activated protein kinase-dependent pathways, leading to cAMP-responsive element-binding protein phosphorylation and microphthalmia-associated transcription factor expression. These findings demonstrate the potential of 5 as a potent therapeutic agent for hypopigmentation.
Keywords: Magnolia biondii; Magnoliaceae; melanogenesis; (+)-magnolin; three-dimensional human skin equivalent; tyrosinase